PMO-026 Re-audit of action on positive H pylori (HP) serology: significantly better … not yet perfect. (28th May 2012) - Srinivas, M; Yeomans, S; Morris, P; Basumani, P; Bardhan, K
Abstract : Introduction: We identified a patient with duodenal ulcer re-bleed whose earlier Hp seropositive result was overlooked, hence not acted on. This triggered an audit 1 of action taken on hospital–initiated Hp seropositive results. It showed inadequate action in 17% due to multiple serology request sources, unclear advice from endoscopists & varied involvement of endoscopy specialist nurses (SpN). As most Hp serology tests were initiated at endoscopy, SpN were made the single point of contact to test, review/action results & confirm eradication by Urea Breath Test (UBT) in seropositives. Two actions were taken in November 2010: a copy of all hospital clinician initiated seropositive results to be sent by Microbiology lab to SpN & a code "ESN" created in the lab system for SpN to request & receive serology results directly. Aim: To re-audit management of Hp seropositive patients since introducing the above measures. Methods: Retrospective study of all hospital clinician initiated Hp seropositive results between January and June 2011 (list from microbiology lab database). Proof of action was got from our Medical Physics UBT database, SpN contact log, Endoscopy reporting software (endoscopist advice on testing & action if positive) and notes review when data not obtainable from these sources. Results: 90 seropositive patients identified; seven excluded from analysis as they died soon after test (cancer in most). Action on Hp positive results: 82/83(99%) results acted upon. One with metastatic cancer was tested (contrary to endoscopist advise) & result overlooked by ward team. SpN reviewed 75/82 (92%) patients and treated 70:69 completed eradication but one did not (adverse reaction to the antibiotics). Five were not treated on advice of the test-requesting clinician. The remaining seven patients were managed by ward staff (treatment advised by SpN) or by patient's General Practitioner (GP) on advice given in the endoscopy report. Post-eradication follow-up UBT: All 69 patients treated by SpN had UBT arranged but 10 defaulted the appointment. No follow-up UBT request was recorded in our hospital for the seven treated by ward staff or GPs. Conclusion: The measures put in place have resulted in near-complete action but gaps in after-care identified: All SpN managed patients had follow-up UBT arranged (15% failed to attend) while those treated by others had no follow-up UBT. Hence our management system is being tightened particularly for patients treated by ward teams & GPs by: Ensuring endoscopy reports give specific advice on Hp treatment and follow-up UBT. SpN to be emailed an additional monthly collated list of seropositives from the Microbiology lab, enabling cross-check to identify/pursue those missed for treatment/follow-up UBT. Competing interests: None declared. Reference: 1. Gut 2011;60 (Suppl 1):A106. Abst PTU094.